The holy blood and the holy grail - Baigent, Michael; Leigh, Richard Lincoln, Henry (Arrow London, 2006)
This is a modern Grail quest leading back through cryptically coded parchments, secret societies, the Knights Templar, the Cathar heretics and a dynasty of obscure French kings